2023
DOI: 10.5694/mja2.51877
|View full text |Cite
|
Sign up to set email alerts
|

The association between child maltreatment and health risk behaviours and conditions throughout life in the Australian Child Maltreatment Study

Abstract: Objective: To estimate associations between all five types of child maltreatment (emotional abuse, neglect, physical abuse, sexual abuse, and exposure to domestic violence) and health risk behaviours and conditions. Design, setting, participants: Nationally representative survey of Australian residents aged 16 years and older conducted by computer-assisted telephone interviewing.Main outcome measures: Associations between child maltreatment and the following health risk behaviours and conditions: current smoke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Our previous research only showed a consistent association between physical and emotional abuse and self-reported suicidal behaviour, while findings for neglect and sexual abuse were mixed, possibly because the study was under-powered. Results from the ACMS similarly reinforce this discrepancy (Lawrence et al , 2023 ). ACMS researchers identified that individuals who self-reported CM had 3.93 higher odds of self-harming in the previous 12 months compared to those who had not experienced CM (after adjustment) (Lawrence et al , 2023 ).…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…Our previous research only showed a consistent association between physical and emotional abuse and self-reported suicidal behaviour, while findings for neglect and sexual abuse were mixed, possibly because the study was under-powered. Results from the ACMS similarly reinforce this discrepancy (Lawrence et al , 2023 ). ACMS researchers identified that individuals who self-reported CM had 3.93 higher odds of self-harming in the previous 12 months compared to those who had not experienced CM (after adjustment) (Lawrence et al , 2023 ).…”
Section: Discussionmentioning
confidence: 71%
“…Results from the ACMS similarly reinforce this discrepancy (Lawrence et al , 2023 ). ACMS researchers identified that individuals who self-reported CM had 3.93 higher odds of self-harming in the previous 12 months compared to those who had not experienced CM (after adjustment) (Lawrence et al , 2023 ). They also reported 4.56 times higher odds of attempting suicide (Lawrence et al , 2023 ).…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations